Survival and factors associated with intensive care unit mortality among adults with impaired consciousness in Benin, a low-resource setting: A retrospective cohort study - Mahunan Gerard Sossou; Dieu donne Gnonlonfoun (PLoS ONE, 2026)
Introduction Impaired consciousness is a common and potentially life-threatening condition that frequently requires admission to intensive care units (ICUs). In sub-Saharan Africa, data on outcomes among critically ill patients with impaired consciousness remain limited, particularly in resource-limited settings. This study aimed to estimate survival and identify factors associated with ICU mortality among adults with impaired consciousness admitted to the ICU of the national referral hospital in Benin. Methods This single-center retrospective cohort study used secondary data from the ICU database covering January 2015 to June 2017. Survival was estimated using the Kaplan–Meier method, and factors associated with ICU mortality were identified using Cox proportional hazards models. Results Among 416 patients, 279 died, yielding an ICU mortality of 67.1%. The median time to death in the ICU was 5 days. Survival probabilities declined from 77.6% on day 1 to 21.9% on day 15 and 13.7% on day 30. In multivariable analysis, older age and lower Glasgow Coma Scale score showed time-varying associations with ICU mortality. Lower systolic blood pressure, higher body temperature, absence of traumatic brain injury, and absence of oxygen therapy were independently associated with higher ICU mortality. Conclusion ICU mortality among adults with impaired consciousness admitted to this ICU was very high. This observation is consistent with constraints in essential critical care resources. Simple clinical parameters available at admission may support early risk stratification. Strengthening essential critical care components, particularly basic physiological monitoring and reliable oxygen supply, warrants consideration in sub-Saharan African ICUs.